(untitled) (Academicia Globe: Inderscience Research, 2023)
Today, the demand for agricultural products, i.e. fruits and vegetables grown in our country, is increasing significantly in the domestic and foreign markets. Therefore, opportunities are being created to produce goods that have their own place in foreign markets by producing ready-made products from the agricultural products grown in our country that meet international standards.